Deciphering the interaction between Twist1 and PPARγ during adipocyte differentiation - Leilei Sun; Shaoping Ji; Xuan Xie; Lei Si; Shaohao Liu; Yao Lin; Yahui Wang; Zhenhua Song; Na Fang; Yang An; Jian Yang (Cell Death and Disease, 2023)
Abstract Obesity, a worldwide epidemic in recent years, is mainly due to the uncontrolled development of adipose tissues, which includes adipocyte hypertrophy and hyperplasia. Adipocyte differentiation is a process involving multiple transcription factor cascades, and the exact mechanism has not yet been defined. As a bHLH transcription factor, Twist1 exerts its activity by forming homo- or heterodimers with other factors. In this study, we showed Twist1 restricts adipogenesis through PPARγ. Expression of various differentiation markers (including PPARγ and adiponectin) and triglyceride-containing lipid droplets were decreased with overexpression of Twist1. Pathway enrichment analysis of RNA-seq data showed that differentially expressed genes (DEGs) caused by Twist1 overexpression were significantly related to lipolysis and PPARγ signaling. This implicates that Twist1 plays important regulatory roles in these processes. ChIP and dual luciferase assays showed that Twist1 could bind either PPARγ or adiponectin promoter to repress their respective transcription or directly to PPARγ protein to regulate its transcriptional activity. Furthermore, Twist1 directly interacted RXRα, which usually forms heterodimer with PPARγ to regulate adipogenesis. Taken together, our results suggest that Twist1 is an inhibitory modulator of adipogenesis and its function is likely through direct interaction with PPARγ protein or its gene promoter.